Tinjauan Lama Waktu Tunggu Pelayanan Pasien Rawat Jalan Poli Jantung di Rumah Sakit Angkatan Laut Marinir Cilandak Tahun 2022 - Fingky Rizki Wulandari; Puteri Fannya; Deasy Rosmala Dewi; Daniel Happy Putra (Pusat Riset dan Inovasi Nasional, 2023)
Patient is a person who, directly or indirectly, consults a doctor or medical service about a health problem in order to receive the medical care the patient needs. After registering, patients need to wait until they get health services from the intended poly. The waiting time is understood as the time required from the arrival of the patient to the moment when the specialist performs the service. This study aims to review the length of waiting time for cardiac outpatient services at the Cilandak Marine Marine Hospital in 2022 using a quantitative approach with descriptive research methods, namely conducting direct interviews with outpatients and directly reviewing the length of waiting time for patients. 74 patient samples, there were 23 patients (31.08%) whose waiting time was appropriate or below the minimum service standard of waiting time (≤60 minutes), while for 51 patients (68.92%) the waiting time did not meet the minimum service standard of time. waiting time (>60 minutes), with an average patient waiting time of 96 minutes. The fastest waiting time for patients is 41 minutes, while the longest waiting time for patients is 173 minutes. Factors that cause long waiting times for outpatients are the inadequate number of medical record officers and medical personnel, the number of patients who come at the same time, causing queues at the registration counter and queues at the poly, doctors' practice hours are quite at odds with registration hours at the counter, negligence of the patient when registering, not carrying a medical card, not carrying the necessary documents, and not the patient concerned who registers, and the number of medical personnel and officers is not sufficient.